Influence of human capital on the performance of organic milk production - Svetlana Ignjatijević; Jelena Vapa Tankosić; Nikola Puvača; Marko Carić; Aleksandar Rajković; Snežana Lekić; Vladimir Tomašević; Bojan Vapa; Radivoj Prodanović (Mljekarstvo)
Over the past decade, a growing interest of consumers in the consumption of organic milk has been recognized, mostly because of its positive effect on human health, besides other various positive effects. The main goal of organic milk production is to bring agricultural production in close alignment with the requirements of a sustainable system. Human capital in organic farming is an important factor as it significantly influences production and financial results. As an important factor in the production, socio-economic characteristics of producers considerably determine possibilities of the future development of this system of production in a certain country. Focusing on the aspect of human capital, this paper examines the possibilities of the development of organic agricultural production in the Republic of Serbia. The research has been conducted on the territory of Serbia on individual farms which are certified for organic farming. Following the findings, the authors conclude that human capital in organic milk production of the Republic of Serbia does not represent a limiting factor in the future development of this system and that human capital in terms of learning and education, experience and expertise, innovation and creativity, and sources of knowledge has a positive relationship with the business performance.